Burn Hypertrophic Scar Profile Based on POSAS Score at Prof. Dr. R. D. Kandou Hospital Manado - Mendy Hatibie; Maximillian C. Oley; Eko S. Sinaga (e-CliniC, 2023)
Burn injury is skin damage due to extreme temperature resulting in hypertrophic scar if impaired of wound healing occurs that can impact on the quality of life. Evaluation of hypertrophic scar objectively and subjectively including scar quality and quality of life patient could performed with POSAS score. This study aimed to evaluate burn hypertrophic scar profile based on POSAS core at Prof. Dr. R. D. Kandou Hospital Manado. This was a retrospective study using medical records of burn patients from 2018 to 2020 at Prof. Dr. R. D. Kandou Hospital. The results obtained 64 samples. Most of the patients were male (75.0%). The most dominant age of patients was over the age of 21 years (79.7%). The most frequent cause of burns was exposure to hot water (71.9%) followed by fire (21.9%). The undergraduate education level was the most affected by burns (79.7%). The type of work most affected was the professional group (62.5%) followed by housewives (18.8%). Most of the wounds were superficial-middermal degree (71%) followed by superficial degree (15,6%) and deep dermal full thickness (12,5%). Assessment of hypertrophic scars using the POSAS score showed almost the same results between observers and patients. In conclusion, hypertrophic scar evaluation with POSAS score is very useful because it can evaluate the scar quality and the quality of life. POSAS score evaluation is depended on wound treatment, duration of wound healing, grading and wound burn area, and length of stay. Keywords: hypertrophic scar; POSAS score; quality of life